Dual decomposition in stochastic integer programming - Carøe, Claus C.; Schultz, Rüdiger (Operations research letters, 1999)
We present an algorithm for solving stochastic integer programming problems with recourse, based on a dual decomposition scheme and Lagrangian relaxation. The approach can be applied to multi-stage problems with mixed-integer variables in each time stage. Numerical experience is presented for some two-stage test problems.